When do organizations learn from successful experience? The Case of Venture Capital Firms - Gerasymenko,Violetta (International Small Business Journal, 2019)
Ability to accurately predict the outcomes of investments in new projects is recognized as an important antecedent of organizational success. Yet, despite the extensive research on resource-allocation decisions and forecasting, we know little about how accumulated experience shapes the accuracy of forecasts. In this study, we investigate the influence of success and failure experiences on the accuracy of venture capital predictions of the outcomes of their portfolio companies. We also explore the moderating influence of an important organizational factor, the size of a decision-making team. Our theory and findings highlight that success and failure experiences have significant and varying impact on the accuracy of organizational predictions. By examining these novel relationships, we extend theorizing about forecasting and learning, and bring novel insights to the field of entrepreneurship and venture capital.
Keywords: Strategy & Entrepreneurship